On the feasibility of identifying first order ogden constitutive parameters of gelatin gels from flat punch indentation tests - Sanchez Fellay, Lucas (2015)
The feasibility of extracting First Order Ogden constitutive parameters of gelatin gels from experimental flat punch indentation curves is analyzed. Eight gelatin gel samples of different formulations are evaluated. Identification of constitutive parameters is carried out by an inverse method that combines finite element modeling simulations and numerical optimization. Parameters are compared with those obtained from uniaxial compression. A parametric study of the influence of model parameters on the shape of curves and a sensitivity analysis of parameter re-identification is performed. Accurate extraction of parameters is possible if the domain in which α parameter stands are lower than 2.